Influence of social deprivation on provision of bariatric surgery: 10-year comparative ecological study between two UK specialist centres. Issue 10 (12th October 2017) - Bhanderi, Shivam; Alam, Mushfique; Matthews, Jacob Henry; Rudge, Gavin; Noble, Hamish; Mahon, David; Richardson, Martin; Welbourn, Richard; Super, Paul; Singhal, Rishi
Abstract : Objective: To investigate the effect of residential location and socioeconomic deprivation on the provision of bariatric surgery. Design: Retrospective cross-sectional ecological study. Setting: Patients resident local to one of two specialist bariatric units, in different regions of the UK, who received obesity surgery between 2003 and 2013. Methods: Demographic data were collected from prospectively collected databases. Index of Multiple Deprivation (IMD 2010) was used as a measure of socioeconomic status. Obesity prevalences were obtained from Public Health England (2006). Patients were split into three IMD tertiles (high, median, low) and also tertiles of time. A generalised linear model was generated for each time period to investigate the effect of socioeconomic deprivation on the relationship between bariatric case count and prevalence of obesity. We used these to estimate surgical intervention provided in each population in each period at differing levels of deprivation. Results: Data were included from 1163 bariatric cases (centre 1–414, centre 2–749). Incidence rate ratios (IRRs) were calculated to measure the associations between predictor and response variables. Associations were highly non-linear and changed over the 10-year study period. In general, the relationship between surgical case volume and obesity prevalence has weakened over time, with high volumes becoming less associated with prevalence of obesity. Discussion: As bariatric services have matured, the associations between demand and supply factors have changed. Socioeconomic deprivation is not apparently a barrier to service provision more recently, but the positive relationships between obesity and surgical volume we would expect to find are absent. This suggests that interventions are not being taken up in the areas of need. We recommend a more detailed national analysis of the relationship between supply side and demand side factors in the provision of bariatric surgery.